OPTIMALISASI PENGAMBILAN KEPUTUSAN PENILAIAN KINERJA DOSEN PADA PERGURUAN TINGGI ISLAM XYZ MENGGUNAKAN AHP (ANALYTICAL HIERARCHY PROCESS): Rahma Farah Ningrum - Jurnal, Redaksi Tim (PETIR, 2019)
In a decision-making process, decision makers are often faced with various problems that come from the diversity criteria. Related to this, the Analytical Hierarchy Process (AHP) can be used to resolve such issues. One is the assessment of islamic university lecturer performance who rely on the criteria of integrity, professional competence, and performance. For the sake of effectiveness of an islamic higher education institution, required a software decision support system such as EC (Expert Choice) that can process data in order to recommend a decision regarding the performance of lecturers that will affect the class and salary increment.